Analysis Of The Effectiveness Of Financial Control In The Toraja Church, Lauwa Congregation, Wajo Regency - Pallame, Junihetty; Mongan, Benyamin; Jaya, Amir (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Study This aiming For evaluate effectiveness control finances at Toraja Church Congregation Lauwa Regency Wajo during period 2021–2023. Approach descriptive quantitative used with method analysis difference between budget and realization reception as well as expenses , plus analysis sources and uses of funds. Research results show that realization reception always beyond budget , reflects effectiveness tall in management income . On the contrary , there is difference in expenditure that shows effectiveness is not yet optimal even though Still within tolerance limits . Analysis source and use of funds indicated that the funds are used in accordance allocation with system good documentation and verification . Findings​ This indicates that control finance church classified as Enough effective , especially in implementation The principles of Stewardship Theory emphasize not quite enough moral responsibility , transparency and accountability in organizational fund management non-profit . Research This give contribution practical for management finance church as well as enrich literature academic related control finances in non-profit based institutions religious .